Indonesia – Singapore Economic Cooperation: Increasing Economic Progress and Regional Development - Syifa Syahrani; Septiani, Risda; Ayu, Wulan; Pebrianti, Anti; Daspar, Daspar (Lentera Ilmu Nusantara, 2024)
Economic cooperation between Indonesia and Singapore continues to be strengthened through various initiatives, focusing on developing SEZ and KEK areas, as well as cooperation in the digital economy. Singapore excels in electronic products, telecommunications, medicines and chemicals. while Indonesia has advantages in petroleum products, gas, food processing and other sectors. It is hoped that investment and technological development will continue to increase the advantages of both countries in the long term. Bilateral cooperation is expected to strengthen trade and investment between Indonesia and Singapore, which has made a major contribution to economic progress and regional development in both countries. Close relations in various economic sectors, including infrastructure, knowledge and technology exchange, and the agricultural sector, continue to be strengthened to advance economic growth and regional development in both countries.